Symmetry aware generation of two-staged particle decays in high-energy physics. Issue 1 (1st February 2023) - Eich, Niclas; Erdmann, Martin; Fischer, Benjamin; Zimmermann, Niklas
Abstract: We present a specialised layer for generative modeling of LHC events with generative adversarial networks. We use Lorentz boosts, rotations, momentum and energy conservation to build a network cell generating a 2-body particle decay. This cell is stacked consecutively in order to model two staged decays, respecting the symmetries across the decay chain. We allow for modifications of the resulting four-vectors in order to model higher order and detector effects. We give an evaluation of the generator quality in a Higgs decay into two Z bosons, further decaying into a muon pair each.